2014
DOI: 10.4236/jdm.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing 10-year coronary heart disease risk in people with Type 2 diabetes mellitus: Framingham versus United Kingdom Prospective Diabetes Study

Abstract: Aims: Previous studies have suggested that the Framingham coronary heart disease risk prediction equation underestimates risk among people with Type 2 diabetes. We compared the 10-year absolute risks of coronary heart disease (CHD) using a Framingham equation and a United Kingdom Prospective Diabetes Study (UKPDS) equation in adults with Type 2 diabetes. Methods: Participants were from a cross-sectional survey of a randomly selected population. There were 461 people with newly (n = 132) or previously diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
4
0
0
Order By: Relevance
“…Men have higher CVD risk scores than women in Malaysia. This result is in line with previous studies [ 3 , 6 , 35 ]. For the 10-year risk of fatal CVD, our findings for men and women with a high-risk CVD risk score (See Table 2 ) were lower than those of South Korea (men: 7.0%, women: 7.0%) and China (men: 33.0%, women: 28.0%) [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…Men have higher CVD risk scores than women in Malaysia. This result is in line with previous studies [ 3 , 6 , 35 ]. For the 10-year risk of fatal CVD, our findings for men and women with a high-risk CVD risk score (See Table 2 ) were lower than those of South Korea (men: 7.0%, women: 7.0%) and China (men: 33.0%, women: 28.0%) [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…This was not surprising as the CVD risk factors among males were consistently worse than females, especially, based on the higher prevalence of smoking status, higher systolic blood pressure, lower HDL level, and higher diabetes comorbidity status. A recent study in 2014 conducted among European diabetics [ 21 ] also demonstrated similar findings, with females having a lower 10-year CVD risk compared to males (13.4% and 18.5%, respectively). Conversely, a study among the Jamaican population showed no significant difference of the 10-year CVD risk between the genders [ 22 ].…”
Section: Discussionsupporting
confidence: 57%
“…Men have higher CVD risk scores than women in Malaysia. This result is in line with previous studies that have found similar results 4,7,24 . For the 10-year risk of fatal CVD, our ndings for men and women with a high-risk CVD risk score (See Table 2) were lower than those of South Korea (men: 7.0%, women: 7.0%)…”
Section: Discussionsupporting
confidence: 94%